Interaction with IGF1 overrides ANXA2-mediated anti-inflammatory functions of IGFBP5 in vivo - Fan, Yan; Wu, Yi-Jin; Guo, Kai; Zhou, Xia-Qing; Abulaiti, Abulizi; Olatunji, Opeyemi Joshua; Ji, Cong-Lan; Zuo, Jian (Frontiers in Immunology, 2025)
BackgroundIGFBP5 is a differentially expressed gene (DEG) between M1 and M2 macrophages. This study explained why it causes opposite effects in different circumstances.MethodsGene expression profiles of various cell subsets were compared by mining a public database. THP-1 cells were treated by siRNAs, recombinant IGFBP5, lipopolysaccharide (LPS), picropodophyllin, IGF1 or the combinations. Clinical implication of IGFBP5 changes was investigated using rheumatoid arthritis (RA) and acute lung injury (ALI) models. IGFBP5-bound and differential proteins were identified by Liquid Chromatography Mass Spectrometry method.ResultsIGFBP5 situated in the center of a network constructed by the DEGs of M0 and M1/2 macrophages. Its expression negatively correlated to inflammation in vitro. When IGFBP5 was silenced, monocytes released more IL-1β and IL-6. NF-κB downstream proteins were overexpressed. IGFBP5 interacted with ANXA2 directly. In ANXA2-silenced cells, it showed no anti-inflammatory effect. Monocytes of adjuvant-induced arthritis rats and RA patients expressed less IGFBP5 than normal controls, but its blood levels increased significantly. Adipocytes secreted large amounts of IGFBP5. This secretion was reinforced by the above sera. IGFBP5 decreased in ALI mice’s blood, while its supplement exacerbated inflammation. By binding to IGF1, IGFBP5 prevented its interaction with IGF1R. An IGF1R inhibitor picropodophyllin antagonized functions of IGF1/IGF1R too, but didn’t reinforce the effects of IGFBP5.ConclusionIGFBP5 eases inflammation by interacting with ANXA2, an activator of NF-κB; as an antagonist of IGF1/IGF1R, IGFBP5 may disrupt immune homeostasis in vivo, due to impairment of the latter’s anti-inflammatory functions; excessive IGFBP from adipocytes would be a pathogenic factor in certain diseases.